2013
DOI: 10.1093/icvts/ivt085
|View full text |Cite
|
Sign up to set email alerts
|

The effect of retrograde autologous priming volume on haemodilution and transfusion requirements during cardiac surgery

Abstract: Retrograde autologous priming is an effective adjunct to decrease the blood transfusion rate, coping with the CPB-related haemodilution and its adverse clinical effects. A RAP volume individualized to each patient offers most benefit as part of a multidisciplinary blood conservation approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…1 As a result of lowered perioperative hematocrit negatively influencing both cerebral autoregulation and postoperative neurologic outcome, low hematocrit levels due to excessive hemodilution should be avoided, and techniques limiting hemodilution could prove beneficial. 18,19 The arterial CO 2 level has been demonstrated to affect cerebral blood flow by altering cerebral vasomotor reactivity. 20 The authors' data also show that ARI decreases with increasing p a CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…1 As a result of lowered perioperative hematocrit negatively influencing both cerebral autoregulation and postoperative neurologic outcome, low hematocrit levels due to excessive hemodilution should be avoided, and techniques limiting hemodilution could prove beneficial. 18,19 The arterial CO 2 level has been demonstrated to affect cerebral blood flow by altering cerebral vasomotor reactivity. 20 The authors' data also show that ARI decreases with increasing p a CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…[8] In a study that was published in 2013 which points the influence of the variations in blood flow and pressure on systemic and cerebral oxygen saturation during CPB found that the maintenance of flow and thus DO2 was more important than the maintenance of mean arterial pressure (MAP). [9] In the same study, a phenylephrine-induced increase in MAP led to the decrease of cerebral oxygen saturation (Sco2) and thus to the DO2 to the brain. Bennett and his colleagues came to the conclusion that in conventional CPB, the reason for cerebral desaturation was the failure to achieve the target of the blood flow rate.…”
Section: Blood Flow During Cpb: Goals and Requirementsmentioning
confidence: 93%
“…All the previous studies that pointed the importance of blood flow do not eliminate the importance of MAP. [9] In every study MAP was kept above the level of 50mmHg excluding periods when there was a surgeon request or unwanted quick falls. Consequently, differences in MAP and the importance that those differences have, can only be compared between the range of 50 and 60mmHg, which is considered as the lower limit of a generally accepted of safe perfusion, and 70 and 80mmHg.…”
Section: Blood Pressure During Cpb: Role and Particularitiesmentioning
confidence: 99%
“…The principle of RAP is that the crystalloid volume of the CPB circuit is replaced with the patient's own blood volume just before commencing CPB. 28 This technique has been studied by many and, although it is not new, there is new interest in it because of its role in blood conservation. Since the CPB circuit is primed with the patient's blood, instead of crystalloid, there is less hemodilution, which reduces the need for subsequent blood transfusion.…”
Section: Cardiopulmonary Bypassmentioning
confidence: 99%